2021
DOI: 10.1186/s13031-021-00382-5
|View full text |Cite
|
Sign up to set email alerts
|

Lockdowns, lives and livelihoods: the impact of COVID-19 and public health responses to conflict affected populations - a remote qualitative study in Baidoa and Mogadishu, Somalia

Abstract: Background Authorities in Somalia responded with drastic measures after the first confirmed COVID-19 case in mid-March 2020, closing borders, schools, limiting travel and prohibiting most group functions. However, the impact of the pandemic in Somalia thereafter remained unclear. This study employs a novel remote qualitative research method in a conflict-affected setting to look at how some of the most at-risk internally displaced and host populations were impacted by COVID-19, what determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 13 publications
4
25
0
Order By: Relevance
“…Nevertheless, there was a signi cant socio-economic impact on the livelihoods of African communities that depend on daily earning wages [38], including in Somalia [39]. Livelihood concerns expressed by participants in this study are similar to those reported in recent studies conducted in Somalia's con ict-affected and displaced communities that similarly reported livelihood interruptions, a decrease in household income, and failure to buy basic food items due to movement restrictions [40,41]. This highlights the intrinsic vulnerability of the populations to multiple shocks and points to the need for future pandemic prevention strategies to speci cally address displaced communities as they cannot observe movement restrictions that hobble their daily earnings for survival.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Nevertheless, there was a signi cant socio-economic impact on the livelihoods of African communities that depend on daily earning wages [38], including in Somalia [39]. Livelihood concerns expressed by participants in this study are similar to those reported in recent studies conducted in Somalia's con ict-affected and displaced communities that similarly reported livelihood interruptions, a decrease in household income, and failure to buy basic food items due to movement restrictions [40,41]. This highlights the intrinsic vulnerability of the populations to multiple shocks and points to the need for future pandemic prevention strategies to speci cally address displaced communities as they cannot observe movement restrictions that hobble their daily earnings for survival.…”
Section: Discussionsupporting
confidence: 66%
“…This highlights the intrinsic vulnerability of the populations to multiple shocks and points to the need for future pandemic prevention strategies to speci cally address displaced communities as they cannot observe movement restrictions that hobble their daily earnings for survival. Other researchers have recognized that such interventions duplicated international responses without being contextualized to local circumstances [41].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 has formed a pandemic that is very different from previous pandemics and covers almost all countries around the world, especially the major economies. In addition to the negative effects on health, the COVID-19 crisis has put both people's lives and livelihoods at risk ( 1 , 2 ). COVID-19 threatens the years of progress in health care, hunger, poverty, and education.…”
Section: Introductionmentioning
confidence: 99%
“…The unprecedented nature of this epidemic generated panic both in the general population and in responders. The Somali public exhibited ambivalence [34] with a large proportion of the population considering COVID-19 as non-existent or irrelevant to Somalia whilst others feared becoming infected [35,36]. This resulted in a situation in which people were simultaneously not practising preventative measures but also not using routine health services for fear of infection.…”
Section: "We Struggled For Quite Some Time With a Better Assessment O...mentioning
confidence: 99%
“…This compromise was illustrative of the influence wielded by religious constituents, the degree to which the government was keen not to alienate them as well as the government's limited capacity to unilaterally enforce closure in the face of opposition. In the end, while schools were successfully closed [35], a brief attempt at a general curfew was ineffective [31] and the closure of mosques was never implemented.…”
Section: "Why We Are Out Of the Blue Creating New Institutions When W...mentioning
confidence: 99%